2013
DOI: 10.5120/10540-4675
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Various Evolutionary Techniques of Load Balancing: A Review

Abstract: For a decade swarm Intelligence deals with the design of intelligent multi-agent systems by taking inspiration from the collective behaviors of social insects and other animal societies. They are characterized by a decentralized way of working that mimics the behavior of the swarm. Swarm Intelligence is a successful paradigm for the algorithm with complex problems. The aim of this review paper is to analyze and compare various swarm intelligence evolutionary techniques of load balancing and conclude the best o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Finite Element Method (FEM) is a numerical analysis technique used to solve complex engineering problems [12]. The methodology of FEM analysis can be summarized as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Finite Element Method (FEM) is a numerical analysis technique used to solve complex engineering problems [12]. The methodology of FEM analysis can be summarized as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Scheduling and load balancing are two of the most important aspects allowing to squeeze performance and optimizing the energy consumption of current parallel and distributed systems. The importance of this topic is reflected in a large number of publications and several surveys as [14][15][16][17][18].…”
Section: Related Workmentioning
confidence: 99%
“…More recently, other nature-inspired optimization methods have been investigated for dynamic load balancing, including Particle Swarm Optimization (PSO). A good review of such methods can be found in [5]. At the best of our knowledge, no other authors have ever attempted to use EO to solve dynamic load balancing.…”
Section: Introductionmentioning
confidence: 97%